ICT in the family context in times of confinement: connectivity and communication experiences of university students - Silva-Castillo, Jorge (2022)
Faced with the health emergency that has occurred since 2020 due to the global coronavirus pandemic (COVID-19), society had to adapt to new contexts with the help of Information and Communication Technologies (ICT).   Face-to-face work was interrupted in its daily activities by the mandatory confinement and at the same time the virtual modality was chosen, which for several years had already been applied in distance higher education and in areas of the digital economy, but now it was strengthened by the need to continue fulfilling the same work specifically in the educational field.  The use of ICT has become an essential element, and under this need social actors with different realities converged, so the present study aimed to reveal which were the forms of access to information and communication by students of the National University of Chimborazo (UNACH) during the year 2020. A quantitative diagnosis of the percentage of connectivity, type of service, with a descriptive non-experimental transactional design in reference to access to technological devices that university students have was performed. The results obtained in this investigation allowed to know that 70% of students of the 4 Faculties that conform the UNACH during the year 2020 made shared use of devices with other members of the family to execute their academic activities and telework within the home.